Maintaining Essential Nutrition Services to Underfive Children in Yemen: A Programmatic Adaptation Amidst the COVID-19 Pandemic - Ferima Coulibaly-Zerbo; Ayoub Al-Jawaldeh; Zita C. Weise Prinzo; Marina Adrianopoli; Eshrak Naji Mohammed Al-Falahi; Shafekah Alahnoumy; Nosheen Mohsan Usman; Fanda Ahmed Moqbel; Latifah Abbas Ali; Mohammed Shroh; Ensegam Mohammed Al-Sakkaf; Abdulrazzaq Musaed; et al. (MDPI AG, 2021)
The World Health Organization (WHO) acknowledged that, as health services divert their attention to the COVID-19 pandemic, the delivery of essential nutrition services may be compromised. This impact may be more pronounced in the context of humanitarian crises, such as the one currently unfolding in Yemen. In line with Pillar 9 of the WHO's COVID-19 Strategic Preparedness and Response Plan, this paper reports on the nutrition program adaptations in Yemen to maintain the delivery of essential nutrition services to under-five children. The process of adaptation focused on the services provided within the nutrition surveillance system (NSS), therapeutic feeding centers (TFC), and isolation units (IU). It was conducted in five steps: (1) situation analysis; (2) development of guidance documents; (3) consultation process; (4) capacity-building programs; and (5) incorporation of programmatic adaptation within nutrition services. As of September 2020, NSS, TFC, and IUs services have shifted their standard operating procedures in line with the context-specific adaptations. The process described in this paper may serve as a case-study for other countries that intend to undertake similar adaptations in their nutrition program to contribute to the implementation of the WHO response plan and maintain the delivery of essential nutrition services to children.